Livestock development policies in sub-Saharan Africa (1) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Livestock development policies in sub-Saharan AfricaSummary report of two CTA/OAU-IBAR regional seminars. West and Central Africa: Abidjan, Côte d Ivoire, 5-9 February 1996; East and Southern Africa: Mbabane, Swaziland, 28 July-1 August 1997.C...